Education for all and children's right to education in Malaysia - Kamaruddin, Zaleha; Sheikh Ahmad, Ismail; Sulaiman, Syahnaz (IIUM Press, 2007)
This article discusses the issue of children s right to education in Malaysia in the context of being a signatory to the United Nations Declaration on Human Rights and the United Nations' Convention on the Rights of the Child. The paper begins by discussing the right to education in Islam and some current developments in the local educational system in the context ofcomplying with the international commitments such as the United Nations Declaration on hildren's Right to Education and the Millennium Development Goals of the United Nations' Development Programme, as well as the Education for All (EFA) movement launched by UNESCO in 1990. It further elaborates on the Malaysian educational system as well as the legal framework established in Malaysia with due emphasis on the issue offree and compulsory primary education and children s right to education in Islam.